The spectrum of functional responses during ABCDE stress echocardiography. (25th November 2020) - Zagatina, A; Ciampi, Q; Cortigiani, L; Borguezan-Daros, C; De Castro E Silva Pretto, J.L; Wierzbowska-Drabik, K; Zanella, H; Merlo, P.M; Djordjevic-Dikic, A; Boshchenko, A; Arbucci, R; Monte, I; et al.
Abstract: Background: The new methodological standard in stress echo (SE) is the comprehensive approach with ABCDE protocol: step A for regional wall motion abnormalities (RWMA); step B for B-lines by lung ultrasound; step C for left ventricular contractile reserve (LVCR); step D for Doppler-based coronary flow velocity reserve (CFVR) in left anterior descending coronary artery; and step E for imaging-independent EKG-based heart rate reserve (HRR). Purpose: To assess the feasibility of ABCDE-SE in a prospective, large scale, multicenter, international, effectiveness study. Methods: From September 2016 to December 2019, we enrolled 4, 585 all-comers patients (age 63±11 years, 2, 566 males, 56%; ejection fraction 61±9%) with known or suspected chronic coronary artery disease referred to clinically-driven SE with exercise (n=1, 774, 38.7%), dipyridamole (n=2, 403, 52.4%), dobutamine (n=375, 8.2%) or adenosine (n=33, 0.7%). Recruitment involved 13-certified laboratories of 7 countries. All patients underwent ABCDE-SE. The same transducer was used for cardiac and lung scan. Criteria for abnormal response were: stress-induced changes in RWMA in 2 contiguous segments for step A; stress-rest increase in B-lines ≥2 for step B (4-site simplified scan, each site scored from 0= A-lines or black lung to 10= white lung for coalescing B-lines); LVCR ≤2.0 for exercise and dobutamine (≤1.1 for vasodilators) for step C; CFVR in LAD ≤2.0 for step D; HRR (peak/rest heart rate) ≤1.80 for exercise and dobutamine (≤1.22 for vasodilators) for step E. Results: Success rate was 98%, 100%, 99%, 86% and 100% for A, B, C, D and E steps, respectively. The positivity rate was 19% for A, 27% for B, 35% for C, 27% for D and 37% for E. All 5 parameters were normal in 1, 496 patients (32.6%), all 5 were abnormal in 183 patients (4.0%). Most patients had abnormal response of 1 (n=1, 356, 29.6%), 2 (n=788, 17.2%), 3 (n=477, 9.7%) or 4 (n=315, 6.9%) criteria (see Figure). Conclusions: ABCDE-SE is extremely feasible, user-friendly, with minimal increase in imaging and off-line analysis time. It allows a comprehensive and personalized functional stratification assessing different vulnerabilities: epicardial coronary artery stenosis (step A), pulmonary congestion (step B), global myocardial dysfunction (step C), coronary microcirculatory dysfunction (step D), and cardiac autonomic nervous system imbalance (step E). The SE response is not only black and white with step A but can be effectively titrated from benign green code (all steps negative) to more functionally malignant red code (at least 3 steps positive). Funding Acknowledgement: Type of funding source: None